Pharmacokinetic profile and first preliminary clinical evaluation of bendamustine in Taiwanese patients with heavily pretreated indolent B‐cell non‐Hodgkin lymphoma and mantle cell lymphoma. Issue 4 (11th August 2014) - Hsiao, Liang‐Tsai; Tien, Hwei‐Fang; Kuo, Ching‐Yuan; Wu, Jin‐Hou; Hou, Hsin‐An; Wang, Ming‐Chung; Liu, Chun‐Yu; Chen, Po‐Min; Chiou, Tzeon‐Jye
Abstract: Prior studies found bendamustine is efficacious in patients with indolent B‐cell non‐Hodgkin lymphoma (NHL). To date, no studies have reported the efficacy of bendamustine in a Chinese population. This multicentre phase II trial evaluated the pharmacokinetics (PK), safety and efficacy of bendamustine monotherapy in Chinese patients in Taiwan with pretreated indolent B‐cell NHL or mantle cell lymphoma (MCL). For PK assessments, patients were randomized ( n  = 16; 11 with indolent B‐cell NHL and five with MCL) to 90 or 120 mg/m 2 of bendamustine for the first cycle. Plasma levels of bendamustine and its two metabolites were analyzed. For efficacy and safety evaluations, bendamustine 120 mg/m 2 was given to all patients every 3 weeks starting at cycle 2 for a minimum of a total of six cycles. The median age of patients was 61.7 years, and the majority were men (75%). The median number of prior treatments was 4 (range, 1–9 regimens), and all patients were previously treated with rituximab. Bendamustine plasma concentration peaked near the end of infusion and was rapidly eliminated with a mean elimination half‐life ( t 1/2 ) of 0.67–0.8 h. Of the evaluable patients ( n  = 14), the overall response rate was 78.6%, including 7.2% of patients having a complete response. Mean progression‐free survival was 27.5 weeks. The most common grade 3–4 adverse events were leucopenia (56.3%), neutropenia (56.3%) and thrombocytopenia (25%). In conclusion, bendamustine was efficacious and well tolerated in Taiwanese patients with indolent NHL and MCL with a similar PK profile to that of other populations. Copyright © 2014 John Wiley & Sons, Ltd.